The Effect of Maternal Micronutrient Supplementation During Lactation on Breast Milk Composition and Infant Nutritional Outcomes: A Systematic Review of Vitamin D, Iron, and Omega-3 Fatty Acids - Allysa; Arlinda (International Medical Journal Corp. Ltd, 2025)
Background : Human milk is the optimal source of nutrition for infants, providing a complex matrix of components essential for growth and development. The composition of breast milk is dynamic and can be influenced by maternal nutritional status. Specific micronutrient supplementation during lactation is a proposed strategy to enhance milk quality and improve infant health outcomes, yet the efficacy of this approach varies significantly by nutrient. Objectives : To systematically review and critically evaluate the evidence from randomized controlled trials (RCTs) on the effects of maternal supplementation with vitamin D, iron, and omega-3 fatty acids during lactation on breast milk composition and a comprehensive range of corresponding infant nutritional, health, and developmental outcomes. Methods : A systematic search of PubMed, Google Scholar, Semanthic Scholar, Springer, and Wiley Online Library was conducted. The review included RCTs of maternal oral supplementation with vitamin D, iron, or omega-3s during lactation in mothers of exclusively or predominantly breastfed infants. Primary outcomes included breast milk composition and infant biochemical status (e.g., serum 25-hydroxyvitamin D, hemoglobin, serum ferritin, red blood cell docosahexaenoic acid). Secondary outcomes included infant anthropometry, neurodevelopment, immune function, gut microbiome composition, allergic disease incidence, and maternal mental health. Results : Vitamin D: High-dose maternal vitamin D supplementation (e.g., 4000–6400 IU/day) robustly increases vitamin D levels in breast milk and is as effective as direct infant supplementation (400 IU/day) in achieving vitamin D sufficiency (serum 25(OH)D >50 nmol/L) in breastfed infants. Maternal iron supplementation has a minimal effect on the iron concentration of breast milk due to tight homeostatic regulation. Postpartum maternal supplementation effectively treats maternal anemia, significantly reducing maternal fatigue and depression. Omega-3 Fatty Acids: Maternal supplementation with omega-3s, particularly DHA, reliably increases their concentration in breast milk. However, large, high-quality RCTs have consistently failed to demonstrate a significant benefit for infant neurodevelopmental or cognitive outcomes, including in long-term follow-ups. Conclusion : The efficacy of maternal micronutrient supplementation during lactation is highly nutrient-specific, dictated by distinct biological transfer mechanisms. High-dose vitamin D supplementation for the mother is a safe and effective public health strategy for preventing infant deficiency. The role of iron supplementation is more nuanced; it is critical for maternal mental health, but direct infant supplementation for healthy term infants is questionable due to potential adverse effects on growth and the gut microbiome. For omega-3s, the evidence does not support claims of cognitive or visual enhancement but points toward a promising role in allergy prevention.